A process perspective on experience co-creation: How pre-trip involvement prompts destination loyalty. (June 2023) - Cao, Limei; Xie, Dengming; Qu, Ying
Abstract: Although the existing literature has suggested that tourists' experience co-creation during or after trips benefits destination loyalty, knowledge of how pre-trip behavior impacts future behavioral intention from a process perspective is limited. To address the gaps, we develop a logic chain linking past behavior, cognition, emotion, and future behavioral intention under a stage-by-stage process of tourists' experience co-creation using the service-dominant logic of value co-creation theory and the self-consistency principle of attitude theory. Empirically, utilizing PLS-SEM and mediation analysis in a survey ( n = 500) and an experiment ( n = 128), we found a serial mediation pathway whereby high-degree pre-trip involvement heightened satisfaction with the co-creation of experience, which increased place identity or place dependence, and which ultimately enhanced destination loyalty. This research is the first attempt to examine the impact of past behavior on future intention for tourists' experience co-creation from a process perspective.